TEMUAN KERAMIK ASING HASIL PENELITIAN ARKEOLOGI DI SULAWESI SELATAN - Muhaeminah Muhaeminah (Balai Arkeologi Yogyakarta, 2012)
Ceramics was one of the artifacts which found in many areas in South Sulawesi that came from various dynasties aged from 12-20 M. From the research report in a number of archaeological sites in South Sulawesi, most of the ceramics found are a fragment and some of them are intact in the people’s house but it came from the wild digging. The existence of those ceramics shows that there’s a trading activity that involves ceramics as the commodity in that centuries.